Acute, sub-acute toxicity and antioxidant activities (in vitro and in vivo) of Reichardia picroide crude extract. (17th August 2017) - Aouachria, Sana; Boumerfeg, Sabah; Benslama, Abderrahim; Benbacha, Faycel; Guemmez, Thoraya; Khennouf, Seddik; Arrar, Lekhmici; Baghiani, Abderrahmane
Abstract: Ethnopharmacological relevance: Reichardia picroide is a species mainly used for alimentary purposes, but it is traditionally known to be used as hypoglycemiant, diuretic, depurative, galactagogue and tonic. Aim of the study: To date, there are no studies corroborating both its safety and antioxidant activities. The objective of the present study, thus, was to assess the safety profile of Reichardia picroide methanolic extract (RPE) and as well as on its antioxidant and antihemolytic activities. Materials and methods: The acute toxicity of RPE was carried out based on OECD guidelines 425. Signs accompanying toxicity and possible death of animals were monitored for two weeks to ascertain the median lethal dose (LD50 ) of the RPE. In sub-acute toxicity study, the extract was administered by gavage at the doses of 250, 500 and 1000 mg/kg/day for 21 consecutive days. The antioxidant activity of RPE was investigated through various methods both in vitro and in vivo . Results: The admistrated doses did not produce mortality or changes in general behaviors of the tested males and females mice. The LD50 was found to be superior to 5000 mg/kg DW. Moreover, daily administration of RPE at doses ranged from 500 to 1000 mg/kg could result in alteration of liver and kidney histology. Significant decrease in liver enzymes (ALT and AST), urea and creatinine levels in female plasma was recorded. The RPE was, in vitro, strong in DPPH scavenging and hemolytic inhibition, benificial in lipid peroxidation inhibition and reducing power. In addition, it exhibited, in vivo, a strong effect on GSH level increasing and lipid peroxidation inhibition in liver and kidney. Conclusions: It can be suggested, based on the results of this study, that the crude extract of Reichardia picroide was non-toxic in acute administration and the use of this extract is safe at doses ≤ 250 mg/kg. This study supports the application of Reichardia picroides in alimentary and traditional medicine purposes. Moreover, antioxidant activity results suggested that Reichardia picroide had potent antioxidant activities and could be utilized as new natural antioxidant in food and therapeutics. Graphical abstract: Highlights: The toxicological profile of Reichardia picroide was investigated. The in vitro and in vivo antioxidant activity was evaluated. LD50 of Reichardia picroide was higher than 5000 mg/kg. Reichardia picroide is safe at doses ≤ 250 mg/kg. Reichardia picroide had potent antioxidant activity both in vitro and in vivo .